Lean on me - Avildsen, John G., 1936-; Freeman, Morgan; Todd, Beverly, 1946-; Guillaume, Robert (Burbank, CA : Warner Home Video, 2010)
Principal Joe Clark, known for his tough-love approach to students, struggles to instill discipline and encourage learning in his New Jersey high school.
Morgan Freeman, Beverly Todd, Robert Guillaume, Alan North, Lynne Thigpen, Robin Bartlett.
MPAA rating: PG-13.
DVD, Dolby digital surround stereo.
Closed-captioned.
Keywords: Clark, Joe, -- 1939 May 8-2020 -- Drama; Eastside High School (Paterson, N.J.) -- Drama; High school principals -- Drama; High school students -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films